Light‐Directed Writing of Chemically Tunable Narrow‐Band Holographic Sensors. Issue 3 (2nd January 2014) - Yetisen, Ali K.; Butt, Haider; da Cruz Vasconcellos, Fernando; Montelongo, Yunuen; Davidson, Colin A. B.; Blyth, Jeff; Chan, Leon; Carmody, J. Bryan; Vignolini, Silvia; Steiner, Ullrich; Baumberg, Jeremy J.; Wilkinson, Timothy D.; et al.
<x xml:space="preserve">Abstract</x> This tunable holographic sensor offers interrogation and a reporting transducer as well as an analyte‐responsive hydrogel, rendering it label‐free and reusable. A single 6 ns laser pulse is used to fabricate holographic sensors consisting of silver nanoparticles arranged periodically within a polymer film. The tunability of the sensor is demonstrated through pH sensing of artificial urine and validated through computational modeling. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>